A proposed mechanism for the MDMA-mediated extinction of traumatic memories in PTSD patients treated with MDMA-assisted therapy - Sottile, Robert J.; Vida, Thomas (Frontiers in Psychiatry, 2022)
Post-traumatic stress disorder (PTSD) is a devastating psychiatric disorder afflicting millions of people around the world. Characterized by severe anxiety, intrusive thoughts, pervasive nightmares, an assortment of somatic symptoms, associations with severe long-term health problems, and an elevated risk of suicide, as much as 40–70% of patients suffer from refractory disease. 3,4-Methylenedioxy-methamphetamine (MDMA), like classic psychedelics such as psilocybin, have been used to enhance the efficacy of psychotherapy almost since their discovery, but due to their perceived potential for abuse and inclusion on USFDA (United States Food and Drug Administration) schedule 1, research into the mechanism by which they produce improvements in PTSD symptomology has been limited. Nevertheless, several compelling rationales have been explored, with the pro-social effects of MDMA thought to enhance therapeutic alliance and thus facilitate therapist-assisted trauma processing. This may be insufficient to fully explain the efficacy of MDMA in the treatment of psychiatric illness. Molecular mechanisms such as the MDMA mediated increase of brain-derived neurotrophic factor (BDNF) availability in the fear memory learning pathways combined with MDMA's pro-social effects may provide a more nuanced explanation for the therapeutic actions of MDMA.